PEMBENTUKAN PERATURAN KEPALA OTORITA IBU KOTA NUSANTARA SEBAGAI PRODUK HUKUM DAERAH BERDASARKAN UNDANG-UNDANG NOMOR 12 TAHUN 2011: Formation of Regulations of The Head of The Nusantara Capital Authority as a Regional Legal Product Based on Law Number 12 of 2011 - Alfian Kelen; Ninuk Wijiningsih (Faculty of Law, Universitas Trisakti, 2025)
Indonesia has officially moved the nation's capital with the issuance of Law Number 3 of 2022 (UU IKN) whereby the nation's capital moves from Jakarta to the Archipelago Capital (IKN) in East Kalimantan Province. As a region with special autonomy, IKN has a special regional government as well. IKN is led and managed (Head of the IKN Authority) who has a ministry-level position who has the right to set regulations for administering the IKN regional government. The identification problem of this research is to analyze the suitability of the mechanism for establishing the Regulation of the Head of the Archipelago Capital Authority with Law Number 12 of 2011. The type of research used is normative legal research. The nature of descriptive research uses secondary data as the main data. Using qualitative data analysis and drawing conclusions deductively. The result and conclusion of the research shows that the mechanism for establishing regulations for the Head of the IKN Authority’s position is not regulated, if the formatting of regulations is unclear and does not comply with the techniques for drafting legislation, the regulations can be canceled based on Article 9 of Law No.12 of 2011.